User-centered design of a longitudinal care plan for children with medical complexity. (12th October 2020) - Desai, Arti D; Wang, Grace; Wignall, Julia; Kinard, Dylan; Singh, Vidhi; Adams, Sherri; Pratt, Wanda
Abstract: Objective: To determine the content priorities and design preferences for a longitudinal care plan (LCP) among caregivers and healthcare providers who care for children with medical complexity (CMC) in acute care settings. Materials and Methods: We conducted iterative one-on-one design sessions with CMC caregivers (ie, parents/legal guardians) and providers from 5 groups: complex care, primary care, subspecialists, emergency care, and care coordinators. Audio-recorded sessions included content categorization activities, drawing exercises, and scenario-based testing of an electronic LCP prototype. We applied inductive content analysis of session materials to elicit content priorities and design preferences between sessions. Analysis informed iterative prototype revisions. Results: We conducted 30 design sessions (10 with caregivers, 20 with providers). Caregivers expressed high within-group variability in their content priorities compared to provider groups. Emergency providers had the most unique content priorities among clinicians. We identified 6 key design preferences: a familiar yet customizable layout, a problem-based organization schema, linked content between sections, a table layout for most sections, a balance between unstructured and structured data fields, and use of family-centered terminology. Discussion: Findings from this study will inform enhancements of electronic health record-embedded LCPs and the development of new LCP tools and applications. The design preferences we identified provide a framework for optimizing integration of family and provider content priorities while maintaining a user-tailored experience. Conclusion: Health information platforms that incorporate these design preferences into electronic LCPs will help meet the information needs of caregivers and providers caring for CMC in acute care settings.